Effect of mica content on mechanical properties of regenerated cellulose nanocomposites via ionic liquids - Abdul Hanid, Nurbaiti (2015)
A series of regenerated cellulose (RC) nanocomposites which were incorporated with the layered silicate mica were successfully prepared via ionic liquid. The effect of the mica loadings was characterized by X-ray diffraction (XRD) and scanning electron microscopy (SEM). The mechanical properties which were investigated via tensile testing indicated that upon the introduction of the mica displayed a significant enhancement on the mechanical stability of the RC. The results showed the potential of mica to reinforce the RC polymers matrix.